Pengaruh Model Perkuliahan Genetika di Jurusan Biologi FMIPA UM terhadap Kemampuan Metakognisi Mahasiswa - Khairil Khairil (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2009)
The aim of this study is to determine the impact of lecture model of Genetics towards students’ metacognition skills based on class category, basic academic skill, and types of subjects. This study was conducted at FMIPA Biology department of UM involving students in education class and non-education class for 2 semester. The instruments used in the research were observation sheets of Genetics lecture, metacognition awareness inventory (MAI), and documents of observation sheet. Anakova with Least Significant Difference (LSD) was used to analyse the data. The result showed that the steps in the lecture model of Genetics comprising instucting reading assessment related to lecture material, composing summary of reading material, setting questions and the answers, and having presentation and discussion. Project-based practical work and classic practical work were used in practical work assessment. Evaluation tools was used based on average score of paper and pencil test and alternative assessment. Students’ metacognition skills were not influenced by class factor (education and non-education, basic academic skill [high or low], and types of Genetics subjects [Genetics I and Genetics II).